The Effect of Family Ownership on the Relationship between Busy Directors and Stock Price Crash Risk for Listed Firms on the Indonesia Stock Exchange - Zachro, Siti Fatimah; Utama, Cynthia Afriani (Jurnal Keuangan dan Perbankan, 2021)
This study explores the impact of busy directors on the stock price crash risk if an individual holds three or more board positions. Since Indonesia has adopted a two-tier system, directors refer to Commissioners. Most of the literature suggests that the main risk factor for stock price crashes arises from the tendency of management to withhold adverse news from investors regarding compensation contracts and career issues. This research aims to verify whether busy directors help to limit managerial opportunistic behavior. Results show that multiple positions bring no effect on the stock price crashes risk due to cross over interaction which negated the substantial effect on the risk of stock price crashes. As a country with high family ownership concentration, the results illustrate that family firms in Indonesia will strengthen the influence of Commissioners who hold multiple positions in reducing stock price crashes risk. This investigation uses a sample of companies listed in the Indonesia Stock Exchange over the period between 2014 and 2019. The generalized method of moment (GMM estimator) is used as a research method to reduce endogeneity problems.DOI: https://doi.org/10.26905/jkdp.v25i1.4909